Energy System Contribution during Competition and High Intensity Swimming Training - Toubekis, Αργύρης; Tokmakidis, Σάββας (Inquiries in Physical Education and Sport, 2008)
Training performed at velocity higher than the velocity of VO2max is characterized as high intensity training and it is often used by competitive swimmers. The knowledge of energy contribution from aerobic and anaerobic metabolism during a competition is essential for planning high intensity training sets for swimmers. Recent studies present an increased contribution from the aerobic metabolism when compared with the data that are reported in older sources. Moreover, for an effective individualised training, the planning of sets aiming to reproduce the energy demands of a competitive event is apparent. The swimming style, (freestyle, breastroke, butterfly or backstroke), and the use of swimming aids such as paddles or swimming resistance, irrespective of sex, do not alter the energy contribution in efforts with the same duration and intensity. The activation of the aerobic and anaerobic metabolism is likely to be altered with age and it is depended on the intensity, the number of repetitions in a set, the duration of the effort as well as on the duration of the recovery. Appropriate selection of the above parameters when planning a training set can activate the energy systems in the same degree as in the competition. High intensity training can maximally activate both the aerobic and anaerobic metabolism and improve competitive performance. The energy contribution from aerobic metabolism is crucial and is considerably increased in repeated efforts, especially when the duration of recovery between repetitions is short. Despite the positive clues on improvement of performance, remains unclear which are the appropriate intensity, recovery duration, number of repetitions and the frequency that can be applied in such a training for each specific event in competitive swimming.